2003
DOI: 10.1161/01.hyp.0000066129.12106.e2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Regulation of ENaC Expression in Kidney by Angiotensin II

Abstract: Abstract-We carried out semiquantitative immunoblotting of kidney to identify apical sodium transporter proteins whose abundances are regulated by angiotensin II. In NaCl-restricted rats (0.5 mEq Na/200 g BW/d), the type 1 angiotensin II receptor (AT 1 receptor) antagonist, candesartan, (1 mg/kg of body weight per day SC for 2 days) markedly decreased the abundance of the ␣ subunit of the epithelial sodium channel (ENaC). This subunit has been shown to be rate-limiting for assembly of mature ENaC complexes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
141
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(156 citation statements)
references
References 39 publications
(48 reference statements)
10
141
1
2
Order By: Relevance
“…This group also demonstrated that angiotensinconverting enzyme is present, allowing Ang II to be formed intraluminally in the collecting duct. 34 Moreover, Beutler et al 10 showed that chronic Ang II infusions stimulate the mRNA expression of the ␣ subunit of the epithelial sodium channel in collecting duct cells of rats and that treatment with a chronic ARB prevents this augmentation. The present study demonstrates further that stimulation of intrarenal AGT by the AT 1 receptor creates an amplification mechanism for the generation of intratubular AGT ultimately leading to increased intratubular formation of Ang I and Ang II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group also demonstrated that angiotensinconverting enzyme is present, allowing Ang II to be formed intraluminally in the collecting duct. 34 Moreover, Beutler et al 10 showed that chronic Ang II infusions stimulate the mRNA expression of the ␣ subunit of the epithelial sodium channel in collecting duct cells of rats and that treatment with a chronic ARB prevents this augmentation. The present study demonstrates further that stimulation of intrarenal AGT by the AT 1 receptor creates an amplification mechanism for the generation of intratubular AGT ultimately leading to increased intratubular formation of Ang I and Ang II.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, epithelial sodium channel gene expression in the cortical collecting duct is also upregulated by Ang II. 10 Thus, Ang II regulates tubular transport in distal as well as in proximal tubular segments via its action on basolateral and luminal receptors. 1 Ang II-infused hypertensive rats exhibit increases in renal angiotensinogen (AGT) mRNA 11 and protein, 12 and an enhancement of urinary excretion rate of AGT.…”
mentioning
confidence: 99%
“…Proximal tubular cells actively produce AngII and also secrete angiotensinogen into the urine (21). Intraluminal angiotensinogen may be converted in the distal tubules to AngII, and recent observations suggest that it leads to induction of sodium channels independent of aldosterone (22). Hyperglycemia and proteinuria could stimulate local AngII synthesis, mainly by oxygen species as signal transducers (12).…”
Section: Local Raasmentioning
confidence: 99%
“…Peti-Peterdi et al [70] demonstrated that Ang II directly stimulates epithelial sodium channel activity in the cortical collecting duct via AT1R. Furthermore, epithelial sodium channel gene expression in the cortical collecting duct is upregulated by chronic infusion of Ang II [71]. Thus, Ang II exerts important effects on tubular transport rate in distal as well as in proximal tubular segments via its action on both basolateral and luminal receptors [65].…”
Section: Tubular Function Of Ras Angiotensin IImentioning
confidence: 99%